Mapeamento do pensamento computacional por meio da ferramenta scratch no contexto educacional brasileiro: análise de publicações do Congresso Brasileiro de Informática na Educação entre 2012 e 2017 - MASSA, Nayara Poliana (2019)
The advance of the technology is growing in an accelerated and continued way. Thus, the use of technology is intrinsic in everyday life. The teaching-learning concepts based on computer science, known as Computational Thinking (CT), are becoming more present each day, inserted in and out of school life, with the aim of transforming people from mere consumers of technology into developers. One of the ways to learn CT concepts is using the software Scratch, which introduces notions of computer programming. This study had the objective to map papers that were published in the Brazilian Congress of Computer Science in Education, between 2012 and 2017, related to CT teaching-learning with Scratch. The methodology used includes a quantitative and qualitative analysis of thirty papers selected after filtering. The quantitative analysis focused on the following: events within the congress and year that was published; target audience; level of schooling; the institution; age; education modality; programs and teaching approach. It was observed that most of the papers about CT with Scratch were published in 2017, coming from eleven Brazilian States. The data indicates that the principal target audience was Middle and High School students (from 6 to 17 years old) in extra curriculum projects carried out in public education institutions. In the perspective of the content, the topics were divided in six sections: a)Scratch and CT teaching at school; b)skills in problem solving; c) building; d) use of technology during classes and day-to-day life; e) fundamental teachings of computer science to teachers; f) environment of developing software in the learning-teaching process. From these classes, the most representative ones were “c” and “d”, in which the highlight is the students as the builders of their own knowledge, development of collaborative work, use of the technology in order to learn and for life. The importance of the Project with CT dimensions demonstrates that the integration of the concepts, practice and computer perspectives develop both technical and conceptual aspects and also human aspects in people’s lives.